Dimethylnitrosamine (DMN) exposed rats: Vernonia amygdalina pre-treatment enhances immunity, hepatic and renal function - Usunobun, Usunomena; Okolie, Ngozi (International Journal of Biological Research, 2016)
Background: The occurrence of dietary and environmental chemicals such as dimethylnitrosamine (DMN) in drinks and foods including fish and meat as well as fresh supermarket products is well established. This study evaluated protective effect of ethanolic leaf extract of Vernonia amygdalina (VAE) on liver synthetic molecules, kidney function and hematological parameters in acute dimethylnitrosamine (DMN)-induced hepatic toxicity in wistar male rats.Methods: Experimental rats divided into four groups of six rats each were used. The first group was untreated and served as control. The second group was orally administered VAE (400 mg/kg) only for seven days. The third group was pre-treated with VAE (400mg/kg) for 7 days and administered 20mg/kg DMN 24hrs after VAE pre-treatment. Rats of the fourth group were given 20mg/kg DMN alone same time with that of group 3. All rats were sacrificed 48hrs after DMN administration.Results: In rats administered 20mg/kg DMN, VAE pre-treatment at 400 mg/kg significantly increased total protein, albumin,White blood cell (WBC), Red blood cell (RBC), Hemoglobin (Hb), packed cell volume (PCV) and Platelets while it significantly decreased total bilirubin, urea and creatinine compared to DMN-alone administered rats.Conclusion: This study suggest that VAE pre-treatment exert its ameliorative effect against DMN-induced hematological and biochemical alterations possibly by preventing the decline of antioxidant defense system and could be prescribed as adjunct to dietary therapy.
Keywords: Dimethylnitrosamine; Hematology; Kidney; Liver; Vernonia amygdalina.